2017
DOI: 10.1083/jcb.201612148
|View full text |Cite
|
Sign up to set email alerts
|

Impaired JIP3-dependent axonal lysosome transport promotes amyloid plaque pathology

Abstract: Axonal lysosomes accumulate abnormally in Alzheimer’s disease brains. However, whether and how such lysosomes contribute to disease pathology has been unclear. Gowrishankar et al. show that the JIP3-dependent transport of axonal lysosomes negatively regulates amyloid precursor protein processing into amyloidogenic peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 61 publications
(118 reference statements)
10
151
0
Order By: Relevance
“…MDVs that are shed by mitochondria may be transported to lysosomes independent of the mitochondrion from which they arose. Furthermore, although lysosomes are most abundant in the soma, there is evidence for lysosomes in axons as well (Ashrafi et al, 2014; Maday and Holzbaur, 2014) and for late endosomes arising in distal axons that mature into lysosomes and increase in their proteolytic capacity en route as they move retrograde (Gowrishankar et al, 2017). The axonal pool of lysosomes may be sufficient to mediate clearance, when needed, in an otherwise healthy neuron.…”
Section: Where Are Mitochondria Cleared?mentioning
confidence: 99%
“…MDVs that are shed by mitochondria may be transported to lysosomes independent of the mitochondrion from which they arose. Furthermore, although lysosomes are most abundant in the soma, there is evidence for lysosomes in axons as well (Ashrafi et al, 2014; Maday and Holzbaur, 2014) and for late endosomes arising in distal axons that mature into lysosomes and increase in their proteolytic capacity en route as they move retrograde (Gowrishankar et al, 2017). The axonal pool of lysosomes may be sufficient to mediate clearance, when needed, in an otherwise healthy neuron.…”
Section: Where Are Mitochondria Cleared?mentioning
confidence: 99%
“…Interestingly, other organelles such as lysosomes show a high dynamics in mature axons, with a tendency for retrograde movement that correlates with their maturation (37). Upon lesion we observed a significant decrease of their velocity.…”
Section: Discussionmentioning
confidence: 60%
“…Anterograde and retrograde movements were equally not affected by axon injury (Figure 5G). In contrast, we observed that lysosomes, tracked with LysoTracker, were extremely motile ( Figure 5K-Q, Video 7A, B), with a bidirectional movement predominantly retrograde, as described for maturing lysosomes tracked with LysoTracker in axons (37). Indeed, 90% of lysosomes were moving (both anterogradely and retrogradely) in intact axons ( Figure 5P) with an average retrograde speed of 0.6µm/s and an average anterograde speed of 0.3µm/s (Figure 5N).…”
Section: /27mentioning
confidence: 51%
“…On the other side, the GWAS-identified genes, CELF1, NME8, and CASS4, are involved in axonal transport (Giri, Zhang, & Lü, 2016). It is important to highlight that impairment of lysosomal axonal transport in AD has been linked to the aggregation of Aβ in the brain of mice (Gowrishankar, Wu, & Ferguson, 2017;Gowrishankar et al, 2015). Finally, genes belonging to endocytosis/trafficking pathways have also been identified as risk factors for AD in several GWAS studies (Karch & Goate, 2015, see Section 4.2 and Table 1).…”
Section: Genetic and Biological Evidence For A Role Of Degradative mentioning
confidence: 99%
“…Neuronal lysosomal dysfunction increases the accumulation of APP-CTFs in endosomal compartments (Boland et al, 2010;Gowrishankar et al, 2017;Guix et al, 2017;Miranda et al, 2018) and its secretion via exosomes (Miranda et al, 2018). Autophagy has been also involved in APP-CTF degradation via the GWAS-identified risk factor PICALM (Tian et al, 2013) although a different study did not find a connection between macroautophagy and APP metabolism (Boland et al, 2010).…”
Section: Enhanced Secretion Of Exosomes May Trigger Increased Aβ Gementioning
confidence: 99%